การหาสภาวะที่เหมาะสมในการสกัดเพกทินจากเปลือกกล้วยหอมทองด้วยกรดไฮโดรคลอริกและกรดซิตริก - อำนวยสิน, นวลกมล; เสือชุมแสง, ณัฐญาภรณ์; เจริญรัตน์, เทพปัญญา (Thai Journal of Science and Technology, 2018)
Abstract Banana (Musa acuminata, AAA group, cultivar ‘Hom Thong’) is one of the most economically important fruit of Thailand. Banana peels represent 30 % of the total weight of fresh banana and the large amount of these peels possesses environmental problem. This research focused on the potential of ‘Hom Thong’ banana peel to be a source of pectin. Effects of acids (hydrochloric acid and citric acid), extraction temperature (85-95 ºC), time (60-180 min) and pH (1.0-3.0) on yield and methoxyl content of extracted pectin were determined using central composite design (CCD). It was found that citric acid was more effective in pectin extraction than hydrochloric acid. Extracted pectin from banana peels with citric acid showed a good physical property and had a high yield. High methoxyl pectin (HMP) and low methoxyl pectin (LMP) were obtained when the peels were extracted by hydrochloric acid and citric acid, respectively. The extraction pH was the main factor affecting yield and methoxyl content of pectin. Furthermore, higher temperatures and times could enhance pectin yield and methoxyl content. By considering yield and methoxyl content, the use of hydrochloric acid at 90 ºC, pH 2.03 with an extraction time of 130 min was the optimal condition for HMP extraction. The yield and methoxyl content under this condition were 14.04 and 9.24 %, respectively. The optimal condition which produced LMP with maximum value of yield and methoxyl content was the use of citric acid at 93 ºC, pH 3.0 with an extraction time of 150 min (16.61 and 6.09 %, respectively). Keywords: ‘Hom Thong’ banana; pectin extraction; optimal condition; yield; methoxyl content